2014
DOI: 10.1136/sextrans-2014-051607
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and risk factors for incident and redetectedChlamydia trachomatisinfection in sexually active, young, multi-ethnic women: a community based cohort study

Abstract: ObjectiveTo investigate the frequency and risk factors for incident and redetected Chlamydia trachomatis infection in sexually active, young, multi-ethnic women in the community.DesignCohort study.Setting20 London universities and Further Education colleges.Participants954 sexually experienced women, mean age 21.5 years (range 16–27), 26% from ethnic minorities, who were recruited to the Prevention of Pelvic Infection (POPI) chlamydia screening trial between 2004 and 2006, and returned repeat postal self-taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 21 publications
3
38
0
Order By: Relevance
“…Another potential explanation is that women with lower socioeconomic status may be less likely to participate in CT screening. 31 In line with Aghaizu et al 7 and Hwang et al, 11 we found that women with a high-risk HPV infection at baseline were at increased risk for incident CT infection. In our study, this association remained after controlling for number of sexual partners and condom use, indicating that the increased risk of CT infection was not explained by more risk-taking sexual behavior among the HPV-positive women.…”
Section: Incident Ct Infectionsupporting
confidence: 85%
See 4 more Smart Citations
“…Another potential explanation is that women with lower socioeconomic status may be less likely to participate in CT screening. 31 In line with Aghaizu et al 7 and Hwang et al, 11 we found that women with a high-risk HPV infection at baseline were at increased risk for incident CT infection. In our study, this association remained after controlling for number of sexual partners and condom use, indicating that the increased risk of CT infection was not explained by more risk-taking sexual behavior among the HPV-positive women.…”
Section: Incident Ct Infectionsupporting
confidence: 85%
“…Based on previous studies, 7,[9][10][11]13,20 we a priori hypothesized that the risk for incident or redetected CT infection may be affected by the woman's age, educational level, age at sexual debut, number of sexual partners during follow-up, condom use, oral contraceptive use, smoking, and high-risk HPV status. In the main analysis, all potential risk factors were measured at baseline, except for "number of sexual partners during follow-up," which was measured at follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations